Assessment of User Preferences in Electric Vehicle Charge Billing System - Maeda, Eva; Rugumila, Georgia; Greyson, Kenedy A.; Gerutu, Gerutu B.; Nyari, Esebi A.; Kivugo, Ramadhani O.; Lujaji, Frank; Chombo, Pius V. (Global Journal of Energy Technology Research Updates, 2024)
Despite the advantages of electric vehicles (EVs), however, their adoption rate in Tanzania remains low. The growth and sustainability of EVs remain questionable due to several factors including an insufficient network of charging infrastructure coupled with billing systems. This study analyzes user preferences related to EV charge billing requirements based on the qualitative assessment of semi-structured interviews with EV users. A survey was conducted around Dar es Salaam city and around 81 sample surveys were administered. The targeted parameters are current EV charge types, daily charging frequency, charging duration, billing system, bill payment, and expectations on public charging infrastructure. The factors were selected to enable an understanding of the drivers for improving acceptance of EV charge billing systems and deduce their market potential. For electric two-wheelers (e2Ws), the findings indicated that 60% of e-bicycle riders charge once per day, 30% charge twice per day, and 10% charge 3 times per day. Moreover, 34% of e-bicycle batteries were charged with 50% of energy remaining in the battery, which took 2 to 3 hours. Contrary, 40.74% of electric three-wheelers (e3Ws) were charging 2 times per day, 33.33% were charging 3 times per day, and 25.93% were charging 1 time per day. In terms of billing, e-bicycles’ charging energy was metered but not billed while e3Ws’ charging energy was not metered but billed at a flat rate regardless of the energy consumed. The majority of EV drivers expected more public charging stations to be equipped with accurate energy measuring systems to enable them to pay-per-use.